Analysis of Air Flow Rate in Bulkhead Reactors on Struvite Mineral - L Edahwati; S Sutiyono; Suprihatin (Biomedical and Mechanical Engineering Journal (BIOMEJ), 2022)
Struvite is a white crystalline chemical known as magnesium ammonium phosphorus hexahydrate (MgNH4PO4.6H2O). Struvite is soluble in acidic conditions and slightly soluble in neutral and alkaline conditions. In industry, struvite is known as scale in pipes. Urinary stones can be called struvite because struvite crystals can form easily in the urine of animals and humans infected with ammonia organisms produced in the urine. Struvite can potentially be formed by alkaline urine and high magnesium excretion due to a high magnesium plant- based diet. The formation of struvite minerals is carried out in an insulated reactor by mixing a solution of MgCl2, NH4OH, and H3PO4 in a ratio of 1:1:1. The treatment of struvite mineral formation was carried out with a feed inlet rate of 35 ml/minute, the temperature at the reactor was carried out at 30oC while the intake air rate was carried out in the range of 0.25-1.25 liters/min. The pH of the solution was kept at a value of 9. The process was carried out until a steady state was reached. The formation of struvite minerals using an insulated column reactor was obtained at conditions of pH 9, operating temperature of 30oC and air rate of 1.25L/min.